Unlocking Vocabulary Mastery: Pocketbook To Meet the Needs of Elementary School Students and Teachers - Tita Ratna Wulan Dari; Alhenri Wijaya; Rasyono Rasyono; Defliyanto Defliyanto (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
The return of English as a subject in elementary school demands help to minimize the students’ vocabulary gap. Therefore, this study aims at seeing the students’ and teachers’ needs on attractive English learning media which can help them enhance the vocabulary mastery. Developing an English pocketbook becomes a solution. Then, as a part of a developmental research, a need analysis study was initially conducted. Applying quantitative design, questionnaires and vocabulary tests were distributed to the respondents. Respondents for this needs’ analysis process were students and teachers at SD Negeri 1 Talang Kelapa. There were 23 respondents, consisting of 1 English teacher, 9 male students, and 13 female students. The questionnaires in Likert scale format were used to check the respondents’ perception, motivation, and anxiety toward English subject at their school. Then, vocabulary tests were given to see students’ vocabulary mastery, both in context and literal meaning. The obtained data from questionnaires and vocabulary tests were then analyzed by using descriptive analysis. Finally, it was found that the students and teachers need a pocketbook which is customized based on their needs. The pocketbook developed needs to address the students’ low achieved vocabulary topics and the students’ anxiety.